BLENDED LEARNING MODEL AS A LEARNING SOLUTION AFTER THE COVID 19 PANDEMIC - Ismail Saleh Nasution; Zulfi Amri; M. Afiv Toni Suhendra Saragih (Proceeding International Seminar of Islamic Studies, 2022)
Since the COVID-19 pandemic hit the world of online learning, it has become a demand in the world of education, especially now that we are facing a new order, namely a new order after the Covid-19 pandemic. Now teachers must find strategies and learning models that can be adapted to this new era. The aims of this research are (1) to explain what is meant by the Blended Learning Model and (2) how the Blended Learning Model is applied to the new post-covid-19 pandemic. This research method uses a literature study using a literature review approach, where scientific papers and articles about the Blended Learning learning model are the main objects of research. The allocation used is 50:50 for face-to-face and online learning. The results of this study are that (1) Learning without utilizing online facilities and face-to-face learning is obtained by a percentage of 0% (2) Utilization of the web in the learning process is 1 to 29% and (3) The learning process uses a combination of web-based teaching materials. and face-to-face by 30-79%. that learning activities using the blended learning model can be used as a learning solution after the Covid-19 pandemicKeywords: Blended Learning, Learning Model, Covid-19